Death and Spirit in Hegel’s Philosophy of Nature - Gelžinytė, Brigita (Problemos, 2024)
The text discusses the problem of the relationship between nature and thinking in Hegel’s Encyclopaedia of the Philosophical Sciences (1830). By considering the dialectics of natural life and the significance of death of the individual for the emergence of spirit in nature, it is argued that spirit, in the Hegelian perspective of speculative thinking, does not emerge from nature as its otherness, as „a more beautiful nature“ that has overcome death. Rather, it appears as a negativity and impotence in nature itself, as the infinite potential of Nature‘s mutability. This highlights the ambivalent unity of nature and thought and the threat of the naturalisation of each.
Keywords: Hegel; nature; life; spirit; negativity